The Quarterly Earnings Predictive of Quarterly Earnings Components (Cash Flow and Accruals) - Ruhupatty, LeRoy Tim (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
This study examines the ability of quarterly earnings components to predict future quarterly earnings using quarterly financial data. This study replicates Dechow and Schrand (2004) test of earnings predictive power, however, using quarterly data. Prior studies have shown that accrual component of earnings is prone to managerial manipulation and, therefore, has low quality. This study contributes to the debate on the quality of earnings components, particularly, by looking at its relevance in a short-term earnings prediction. Consistent with Dechow and Schrand (2004) it is found that accrual component of earnings can predict earnings two (2) quarters and three (3) quarters ahead while cash flow component can predict earnings two (2) quarters ahead. This findings indicate that accrual component of earnings can be used for longer period prediction (2 and 3 quarters ahead) while cash flow component of earnings can be used for shorter period prediction (2 quarters ahead). The use of quarterly earnings reveals that unaudited interim financial information has relevance.